PEMANFAATAN DAN SIKAP MASYARAKAT SEKITAR TERHADAP RAFFLESIA ZOLLINGERIANA KOORD. DAN KONSERVASINYA DI TAMAN NASIONAL MERU BETIRI - Dewi Lestari; Nanang Joko Rianto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2019)
Conservation efforts will succeed if it involves the community so that the utilization of certain species and the attitude of the surrounding community are very important to be known. This study aims to find the utilization of Rafflesia zollingeriana so far and how the attitudes of the surrounding community towards R. zollingeriana, as well as its conservations. R. zollingeriana has been collected by the community around Meru Betiri National Park (MBNP) to be utilized as medicinal materials. The survey results indicated that the community's knowledge and awareness towards R. zollingeriana and its conservation are still low. Utilization of R. zollingeriana mainly occurs due to its economic value. Hence the adopted conservation policy must integrate sustainable use and economic interests of the surrounding community. The recommended form of conservation for R. zollingeriana is ecotourism. This activity should involve relevant stakeholders, among others the community, MBNP, local government, private sector, NGOs, researchers, and academics. There are two proposed areas for the development of R. zollingeriana ecotourism, namely Teluk Hijau and Sukamade beaches. The management of these two locations must pay attention to the aspects of the prevention, mitigation, and recovery. In addition, it is recommended to carry out routine inventory and propagation activities of R. zollingeriana by involving the collaboration of stakeholders, so that the population of R. zollingeriana in MBNP can be sustained for various purposes.